Reliability and measurement error of the Osteoarthritis Research Society International (OARSI) recommended performance-based tests of physical function in people with hip and knee osteoarthritis. Issue 11 (November 2017) - Dobson, F.; Hinman, R.S.; Hall, M.; Marshall, C.J.; Sayer, T.; Anderson, C.; Newcomb, N.; Stratford, P.W.; Bennell, K.L.
Summary: Objective: To estimate the reliability and measurement error of performance-based tests of physical function recommended by the Osteoarthritis Research Society International (OARSI) in people with hip and/or knee osteoarthritis (OA). Design: Prospective repeated measures between independent raters within a session and within-rater over a week interval. Relative reliability was estimated for 51 people with hip and/or knee OA (mean age 64.5 years, standard deviation (SD) 6.21 years; 47% females; 36 (70%) primary knee OA) on the 30s Chair Stand Test (30sCST), 40m Fast-Paced Walk Test (40mFPWT), 11-Stair Climb Test (11-step SCT), Timed Up and Go (TUG), Six-Minute Walk Test (6MWT), 10m Fast-Paced Walk Test (10mFPWT) and 20s Stair Climb Test (20sSCT) using intra-class correlation coefficients (ICC). Absolute reliability was calculated using standard error of measurement (SEM) and minimal detectable change (MDC). Results: Measurement error was acceptable (SEM < 10%) for all tests. Between-rater reliability was: optimal (ICC > 0.9, lower 1-sided 95% CI > 0.7) for the 40mFPWT, 6MWT and 10mFPWT; sufficient (ICC >0.8, lower 1-sided 95% CI > 0.7) for 30sCST, 20sSCT; unacceptable (lower 1-side 95% CI < 0.7) for 11-step SCT and TUG. Within-rater reliability was optimal for 40mFPWT, and 6MWT; sufficient for 30sCST and 10mFPWT and unacceptable for 11-step SCT, TUG and 20sSCT. Conclusions: The 30sCST, 40mFPWT, 6MWT and 10mFPWT, demonstrated, at minimum, acceptable levels of both between and within-rater reliability and measurement error. All tests demonstrated sufficiently small measurement error indicating they are adequate for measuring change over time in individuals with knee/hip OA.